Soft-In Soft-Out Detection Using Partial Gaussian Approximation - Guo, Q.; Huang, D.; Nordholm, Sven; Xi, J.; Ping, L. (IEEE Access, 2014)
This paper concerns the soft-in soft-out detection in a coded communication system, where thetransmitted symbols are discrete valued, and the exact a posteriori probability (APP) detection often involves prohibitive complexity. By using the properties of Gaussian functions, an approximate approach to the APP detection is devised with the idea that, in the computation of the APP of each symbol, the remaining symbols are distinguished based on their contributions to the APP of the concerned symbol, and the symbols with less contributions are approximated as (continuous) Gaussian variables [hence the name partial Gaussian approximation (PGA)] to reduce the computational complexity. The connection between the PGA detector and the reduced dimension maximum a posteriori detector (RDMAP) is investigated. It is shown that, PGA isequivalent to RDMAP, but it has a complexity much lower than that of RDMAP, i.e., PGA can be regarded as an efcient implementation of RDMAP. In addition, the application of PGA in intersymbol interference (ISI) channel equalization is also investigated.We show that PGA allows further signicant complexity reduction by exploiting the circulant structure of the system transfer matrix, which makes PGA very attractive in handling severe ISI channels with large memory length.